Mass spectrometric quantification of urinary human liver fatty acid binding protein in renal transplant recipients. (1st February 2016) - Ozcan, Filiz; Akbas, Halide; Kırac, Ebru; Suleymanlar, Gultekin; Aslan, Mutay; Yucel, Gultekin
Abstract : Rationale: Urinary liver fatty acid binding protein (L‐FABP) has been evaluated as a promising early biomarker of renal ischemia in human kidney transplant patients. The use of L‐FABP in clinical practice requires that this biomarker be associated with an analytical method that combines specificity, accuracy and robustness. This study aimed to evaluate an optimized multiple reaction monitoring (MRM) method using ultrafast liquid chromatography coupled with tandem mass spectrometry to measure urinary L‐FABP levels in renal transplant recipients. Methods: Purified recombinant human L‐FABP tryptic standard was analyzed by matrix‐assisted laser desorption/ionization time‐of‐flight (MALDI‐TOF) mass spectrometry (MS/MS) and liquid chromatography (LC)/MS/MS to select for peptides that provided specificity and adequate response in developing an MRM method for urinary L‐FABP quantification. Human urine samples collected from kidney transplant recipients were isolated, concentrated, precipitated and trypsin digested before mass spectrometric analysis of L‐FABP. L‐FABP levels were also measured in urine samples by enzyme immunoassay. Results: The tryptic peptide ion MH + of 50 FTITAGSK 57 ( m / z 824) provided an adequate signal and was used for quantification of L‐FABP under conditions employed for LC/MS/MS analysis. MALDI‐TOF‐MS/MS spectra obtained by collision‐induced dissociation of the parent MH + ion 50 FTITAGSK 57 resulted in a y 3 product ion that was used for quantitative analysis by the MRM method. Urinary L‐FABP content measured by both ELISA and LC/MS/MS after transplantation was significantly higher compared to before transplantation levels. The Spearman correlation coefficient between the two methods was statistically significant. Intra‐day and inter‐day coefficients of variation provided good repeatability and reproducibility for validation of LC/MS/MS analysis. Conclusions: LC/MS/MS quantification of L‐FABP may provide a new reference method to determine changes in this potential biomarker in human kidney transplant patients. Copyright © 2016 John Wiley & Sons, Ltd.